Before and after Babel: writing as resistance in Ancient Near Eastern Empires - Van de Mieroop, Marc (Oxford University Press, 2023)
The ancient Near East is not only where the world's earliest writing system, Babylonian cuneiform, was invented some 5,000 years ago, but also where nearly 2,000 years later numerous other scripts developed each to write a specific language. As a framework for the rich intellectual history of this region's ancient past, this book investigates how this "confusion of tongues" came about, how writings in the multiple languages and scripts interacted with each other, and what the consequences were.